Sea Ice and Migration of the Dolphin and Union Caribou Herd in the Canadian Arctic: An Uncertain Future - Poole, Kim G.; Gunn, Anne; Patterson, Brent R.; Dumond, Mathieu (ARCTIC, 2010)
Caribou (Rangifer tarandus groenlandicus × pearyi) of the Dolphin and Union herd migrate across the sea ice between Victoria Island and the adjacent Canadian Arctic mainland twice each year, southward in fall–early winter and northward in late winter–spring. As a result of warmer temperatures, sea ice between Victoria Island and the mainland now forms 8–10 days later than it did in 1982, raising questions about the impact of delayed ice formation on the ecology of the herd. We examined movements of female Dolphin and Union caribou as they relate to sea-ice crossings using four satellite collar datasets (46 caribou) obtained between 1987 and 2006. Since the late 1980s, Dolphin and Union caribou have been moving by early October to the southern coast of Victoria Island, where they stage until sea-ice formation allows migration across the sea ice to winter range on the mainland. Caribou spending the summer farther north on Victoria Island arrive later at the coast, which shortens their time spent on the staging area. During the study period, the collared caribou began crossings as soon as sea-ice formation allowed. Most caribou departed from just a few areas and tended to use the same departure areas each year. Highest mortality occurred during the fall–early winter ice crossing and in mid to late winter. Our research raises the question of how the Dolphin and Union caribou will persist in supporting harvesting if the crossing becomes riskier for them or if the seasonal migrations between Victoria Island and the mainland are interrupted. Les caribous (Rangifer tarandus groenlandicus × pearyi) du troupeau Dolphin-et-Union migrent en passant sur la glace de mer entre l’île Victoria et la partie continentale adjacente de l’Arctique canadien deux fois par année, se dirigeant vers le sud à l’automne et au début de l’hiver, et vers le nord à la fin de l’hiver et au printemps. En raison des températures plus chaudes, la glace de mer entre l’île Victoria et la partie continentale se forme maintenant de huit à dix jours ...